5-chloro-1H-benzotriazole and potassium sorbate as binary corrosion inhibitor of copper in acidic solution - Žaklina Tasić; Mihajlović Marija Petrović; Milan Radovanović; Milan Antonijević (Zaštita Materijala)
The effect of potassium sorbate as well as 5-chloro-1H-benzotriazole - potassium sorbate on the corrosion behavior of copper in acidic sulfate media containing Cl- ions was examined. For this purpose, the electrochemical methods and quantum chemical calculations were used. The inhibition efficiency in the presence of 5-chloro-1H-benzotriazole - potassium sorbate was higher than in the presence of potassium sorbate. Also, the inhibition efficiency of binary inhibitor depends on the concentration of Cl- ions added in sulfate solution. According to the results obtained by potentiodynamic polarization measurements, both potassium sorbate and 5-chloro-1H-benzotriazole - potassium sorbate behave as mixed type inhibitors. Quantum chemical parameters are in good agreement with results obtained by electrochemical measurements.